An Eye on Vision: Five Questions About Vision Screening and Eye Health—Part 2. (July 2018) - Nottingham Chaplin, P. Kay; Baldonado, Kira; Cotter, Susan; Moore, Bruce; Bradford, Geoffrey E.
Current evidence-based and best practice vision screening and eye health approaches, tools, and procedures are the result of revised national guidelines in the last 3 years and advances in research during the past 18 years. To help the busy school nurse, with little time to keep up with changes in children's vision practices and a growing body of literature, the National Center for Children's Vision and Eye Health at Prevent Blindness is providing answers to five questions that are often received from the field. Topical areas include (1) which numbers to record when using a 10-foot chart, (2) instrument-based screening and visual acuity, (3) screening children who wear glasses, (4) referring children who do not pass color vision deficiency screening, and (5) conducting near visual acuity screening monocularly or binocularly.